Management Of Metallurgical Enterprises Based On The Introduction Of Financial Analysis - Yusupkhodjaeva G.B. (Peerian Journals Publishing, 2024)
This article discusses the role of financial analysis in the management of metallurgical enterprises. In the light of modern challenges and market requirements, the introduction of financial analysis is an important tool for making strategic decisions and ensuring the sustainable development of enterprises. The article examines key aspects of financial analysis, including analysis of financial statements, performance indicators, comparative analysis and modeling. Special attention is paid to the application of financial analysis to optimize management decisions, improve financial stability and increase the competitiveness of metallurgical enterprises. In conclusion, the article emphasizes the importance of integrating financial analysis into management practices and strategic planning to achieve success in today's dynamic economic environment
Keywords: Metallurgy; management; efficiency; method